Edukasi Digitalisasi Keuangan Syariah Bagi Guru Sebagai Upaya Membangun Literasi Finansial Siswa Mts. Lab. Ikip. Al-Washliyah Medan - Munawaroh; Muhammad Radian Syah; Sri Fitria Jayusman; Asmawarna Sinaga; Riyan Pradesyah; Melisa Zuriani Hasibuan; Rizqy Fadhlina Putri (CV. BAROKAH PUBLISHER, 2026)
The rapid development of Islamic financial digitalization in line with financial technology advancements has not been fully accompanied by adequate Islamic financial literacy among students. This condition highlights the importance of strengthening teachers’ capacity as strategic educational agents in instilling financial knowledge and behavior aligned with Sharia principles from an early age. Therefore, this community service program aims to provide education on the digitalization of Islamic finance for teachers at MTS. Lab. IKIP Al-Washliyah Medan as an effort to enhance students’ financial literacy. The service activities were implemented through stages of socialization, interactive training, simulations of Islamic digital financial services, as well as discussions and mentoring. The materials covered basic concepts of Islamic financial literacy, an introduction to Sharia-based digital financial products and services, and strategies for integrating financial literacy into classroom learning. Evaluation was conducted using pre-test and post-test instruments to measure participants’ improvement in understanding. The results indicate a significant increase in teachers’ understanding of the concepts and practices of Islamic financial digitalization, along with improved readiness to integrate financial literacy into the learning process. This program contributes to strengthening teachers’ roles as agents of Islamic financial literacy and supports the development of financially literate, technologically adaptive students who uphold Islamic economic values.